2009
DOI: 10.1186/bf03353179
|View full text |Cite
|
Sign up to set email alerts
|

Remanence anisotropy effect on the palaeointensity results obtained from various archaeological materials, excluding pottery

Abstract: The effect of magnetic anisotropy on the palaeointensity results has been evaluated in different materials, including samples from archaeological structures of various ages, such as baked clay from prehistoric domestic ovens or pottery kilns, burnt soil from ancient fires, and bricks and bricks or tiles used in the kiln's construction. The remanence anisotropy was estimated by the thermoremanent (TRM) anisotropy tensor and isothermal remanence (IRM) tensor methods. The small anisotropy effect (less than 5%) ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…6; Supplementary material: Table S3; Kovacheva et al, 2009b). As expected, a low TRM anisotropy effect upon archaeointensities was found for the kilns, for which very low differences between uncorrected and TRM corrected intensities were generally obtained (Fig.…”
Section: French Kilns and Bricks Used For The Construction Of Historisupporting
confidence: 74%
“…6; Supplementary material: Table S3; Kovacheva et al, 2009b). As expected, a low TRM anisotropy effect upon archaeointensities was found for the kilns, for which very low differences between uncorrected and TRM corrected intensities were generally obtained (Fig.…”
Section: French Kilns and Bricks Used For The Construction Of Historisupporting
confidence: 74%
“…The difference 90-INC is the angular deviation of the laboratory field from the carried NRM vector. As described in Kovacheva et al, (2009b) and as well known from the literature (Odah et al, 2001), this deviation is one of the main factors for the effect of the magnetic anisotropy during the PI evaluation. For example, on a subset of 44 brick specimens the 12 anisotropy effect on the PI evaluations has been studied using the TRM anisotropy tensor (18) or the ARM anisotropy tensor (26).…”
Section: Discussion Of the Raw Datamentioning
confidence: 72%
“…These values seem to be typical of baked clays, for example, Kovacheva et al (2009) reported that baked clay and soils collected from archeological sites in France and Bulgaria resulted in TRM anisotropy ratios less than 1.20 for about 80% of the collection. …”
Section: Tsunakawa-shaw Paleointensity Experimentsmentioning
confidence: 99%